THE EVOLUTION OF GAME DESIGN IN THE CONTEXT OF MOBILE TECHNOLOGIES (International Journal of Engineering and Computer Science, 2025)
This article explores the retrospective trajectory of game design through the lens of mobile technology development. The rapid pace of technological advancement has profoundly reshaped the landscape of video games, prompting the industry to move away from established conventions in favor of new design paradigms. In an environment marked by intense competition and constantly shifting user behavior, there is an urgent need to rethink the principles behind mobile game development. The aim of this study is to identify and characterize the key vectors driving the evolution of game design under the influence of the mobile environment, examine the nature of methodological shifts, and outline emerging directions for future development. Academic interest in the topic arises from the tension between the push for technological standardization and the growing demand for deeply personalized player experiences. Unresolved challenges also remain in balancing artistic expressiveness with commercial pragmatism, particularly within the prevailing microtransaction-based monetization models. The article discusses changes in design decisions, revisions to player interaction models, and the integration of AI into development workflows. It concludes that mobile game design has moved beyond a phase of imitating platform-based practices and entered a stage of maturity defined by adaptability, fragmented structural logic, and multisensory engagement. The insights presented here will be valuable to professionals in digital development, game designers, interface researchers, and educators working with interactive technologies.